Living losses in stroke caregiving: a qualitative systematic review of systematic reviews on psycho-socio-emotional challenges and coping mechanisms - Choo, Ping Ying (2023)
Stroke compromises the quality of life and wellbeing of stroke survivors and families as a whole. The unexpected caregiving responsibilities often cause psychological distress, overwhelming emotions, living losses and grief, and relational conflicts with stroke survivors. Despite the increasing research to better understand their needs, empirically sound and holistic psychosocial interventions for stroke caregivers are lacking.